The citizens ‘psychological perception of housing in the environment of the housing crisis in Central Europe: Pardubice case study - Maštálka, Martin; Mandys, Jan (My University, 2024)
One of the problems in contemporary Europe is the high real estate prices, which do not allow young couples to start their professional careers and family life in places that would suit them. Such problems cause social and economic problems. Public administration is trying to create building-favorable conditions at the level of the state, regions, or counties, as well as individual municipalities. Market pressures on rising housing prices have at least partially eased. In order for such a procedure to achieve the desired results, a coordinated policy must be developed and implemented in accordance with modern approaches to the management of municipalities, cities, and regions. Such a policy also includes the principles of strategic planning in the case of housing issues summarized in the concept of housing development. The aim of the paper is to identify the key points in the process of preparing the housing concept for a medium-sized city. There was used a mix of personal interviews and questionnaires spread by the important actors in local social policy. The outputs from the research led to the concluding recommendations for the improvement of the housing situation at the local level.
Psychologické vnímání bydlení občanů v prostředí bytové krize ve střední Evropě: Případová studie Pardubice
Keywords: social policy; housing policy; housing development concept; housing support; regional development; city management; sociální politika; bytová politika; koncepce rozvoje bydlení; podpora bydlení; regionální rozvoj; vedení města